Stealing Fire: Political Re-Appropriation of Verse Drama in Tony Harrison’s Prometheus and Liz Lochhead’s Medea - Harriet MacMillan (Forum, 2016)
Critical opinion of verse drama has long considered it to be an outdated and classist form. Yet in the early 21st century, certain dramatists have provided examples of how the form may be subverted not only to expose its privileged history but to provide a context for new lines of ideological enquiry. This article examines how verse drama has been re-appropriated to serve as a vehicle for socialist and feminist concerns in Liz Lochhead's Medea and Tony Harrison's Prometheus.